Study on Anti-Magnetic Pollution Ability of Ni-Cd Battery. Issue 1 (December 2020) - Xu, Chaoqun; Han, Xiaodong; Liu, Chaobo; Meng, Lifei; Xiao, Qi; Yi, Zhong
Abstract: Ni-Cd battery pack is an important part of spacecraft, and its performance is easily affected by the changing magnetic field. In order to grasp the anti-magnetic pollution ability of the battery pack, this paper conducted a charge and demagnetization test study on the battery pack in a magnetic field environment simulation site by adjusting the intensity, frequency, waveform and other magnetic parameters to investigate the charging and demagnetizing effect of the battery pack. The results show that the Ni-Cd battery pack has weak resistance to magnetic pollution and is easily magnetized. In addition, when the magnetic strength is 4.5 mT and the frequency is 1.5 Hz, the demagnetization in three directions of the Ni-Cd battery pack can be well accomplished. This study provides a reference for the use of Ni-Cd battery packs in the magnetic environment and the removal of magnetic pollution effects.